2006
DOI: 10.1160/th06-07-0383
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the von Willebrand factor genotype in UK patients diagnosed to have type 1 von Willebrand disease

Abstract: SummaryForty families diagnosed by UK centres to have type 1 VWD were recruited. Following review, six families were re-diagnosed to have type 2 VWD, one to have a platelet storage pool disorder, and one family was determined to be unaffected. Direct DNA sequencing of the promoter region and all exons and intronic boundaries of the VWF gene identified six mutations likely to be causative of VWD in index cases of nine of the 32 (28%) confirmed type 1 VWD families. These included R1205H (3614G>A) VWD Vicenza,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(11 citation statements)
references
References 23 publications
(41 reference statements)
0
10
1
Order By: Relevance
“…mutation screening of the VWF gene has limited general utility in genetic diagnostic and family studies in Type 1 VWD." 19 This is also seen in Type 3 VWD, where one study found that in approximately 15% of Type 3 VWD patients, two null mutations in the VWF gene were not observed, suggesting other genes may play a role. 20 Taken together, the current state of the literature on VWD type 1 and low-VWF is indicative of a complex disorder with multiple genetic risk factors.…”
Section: Vwd Due To Genetic Variants Outside the Vwf Genementioning
confidence: 90%
See 1 more Smart Citation
“…mutation screening of the VWF gene has limited general utility in genetic diagnostic and family studies in Type 1 VWD." 19 This is also seen in Type 3 VWD, where one study found that in approximately 15% of Type 3 VWD patients, two null mutations in the VWF gene were not observed, suggesting other genes may play a role. 20 Taken together, the current state of the literature on VWD type 1 and low-VWF is indicative of a complex disorder with multiple genetic risk factors.…”
Section: Vwd Due To Genetic Variants Outside the Vwf Genementioning
confidence: 90%
“…This figure is even lower in low‐VWF patients, whose VWF levels are more often explained by synthesis/secretion and not overactive clearance 18 . After discovering only half of their Type 1 patients had any variants in the VWF gene, one group concluded that due to incomplete penetrance and variable expressivity “…mutation screening of the VWF gene has limited general utility in genetic diagnostic and family studies in Type 1 VWD.” 19 This is also seen in Type 3 VWD, where one study found that in approximately 15% of Type 3 VWD patients, two null mutations in the VWF gene were not observed, suggesting other genes may play a role 20 …”
Section: The Vwf Genementioning
confidence: 99%
“…We found a slightly lower prevalence of VWF gene variants compared to some previous studies, probably because we have excluded synonymous variants and benign variants. 5,10–17 In line with our study, it was previously described in one study that in VWD patients with normal multimers, patients without a VWF gene variant had higher VWF:RCo compared with patients with a VWF gene variant. 5 However, no significant difference in the BS of both groups were found, probably due to the small number of included patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although several previous studies reported that approximately 30% to 45% of type 1 VWD patients do not have a VWF gene variant, no large studies have been performed yet to investigate whether the laboratory and bleeding phenotype of type 1 VWD patients with and without a VWF gene variant are different. 3,5,10–17…”
Section: Introductionmentioning
confidence: 99%
“… 10 Patients with VWF levels below 0.50 IU/mL should receive a diagnosis of type 1 VWD if they present with abnormal bleeding. These guidelines, along with other published data, 11 , 12 , 13 , 14 demonstrate a lack of correlation between bleeding severity and baseline VWF levels. This discrepancy complicates risk stratification of patients with type 1 VWD and often leads to homogeneous therapeutic management, creating potential for both over and under treatment of bleeding symptoms.…”
Section: Introductionmentioning
confidence: 98%